Entrepreneurial intentions of urban youth in Vietnam's digital economy: An extended TPB analysis - Thang, Le Ngoc (Edelweiss Applied Science and Technology, 2026)
This study examines the determinants of entrepreneurial intentions among young people aged 18 to 35 in Hanoi, Vietnam. The rapid expansion of digital platforms, fintech services, and e-commerce in recent years has reshaped how urban youth approach entrepreneurship, yet empirical evidence on this group remains limited. We extend the Theory of Planned Behavior by adding perceived risk and test the resulting model on survey data from 376 respondents. The analysis applies exploratory factor analysis in SPSS 29, confirmatory factor analysis in AMOS 24, and structural equation modeling. The results show three main patterns. Perceived self-efficacy has the strongest positive effect on perceived behavioral control, while perceived risk has a negative effect, supporting the inclusion of risk in the TPB framework. Attitude toward entrepreneurship and perceived behavioral control together explain 52.4% of the variance in entrepreneurial intention, and subjective norms contribute both directly and through perceived behavioral control. Respondents from business-owning families report higher intentions, which suggests that early exposure influences intention through psychological mechanisms. The findings provide guidance for educators, training providers, and policymakers working in Vietnam's digital startup ecosystem: building self-efficacy, reducing the psychological weight of perceived risk, and strengthening social support around the entrepreneurial choice.